Perbandingan Tujuan Pola Kerja Yayasan di Beberapa Negara dan Kemungkinan Penerapannya di Indonesia - BPHN (BPHN, 2013)
Perbandingan Tujuan Pola Kerja Yayasan di Beberapa Negara dan Kemungkinan Penerapannya di Indonesia